A population-based case-control study of hospitalisation due to head injuries among bicyclists and motorcyclists in Taiwan. Issue 11 (8th November 2017) - Pai, Chih-Wei; Chen, Yi-Chu; Lin, Hsiao-Yu; Chen, Ping-Ling
Abstract : Introduction: According to official statistics in Taiwan, the main body region of injury causing bicyclist deaths is the head, and bicyclists are 2.6 times more likely to be fatally injured than motorcyclists. There is currently a national helmet law for motorcyclists but not for bicyclists. Objectives: The primary aim of this study was to determine whether bicyclist casualties have higher odds of head-related hospitalisation than motorcyclists. This study also aims to investigate the determinants of head injury-related hospitalisation among bicyclists and motorcyclists. Methods: Using linked data from the National Traffic Accident Dataset and the National Health Insurance Research Database for the period 2003–2012, this study investigates the crash characteristics of bicyclist and motorcyclist casualties presenting to hospitals due to motor vehicle crashes. Head injury-related hospitalisation was used as the study outcome for both road users to evaluate whether various factors (eg, human attributes, road and weather conditions, vehicle characteristics) are related to hospital admission of those who sustained serious injuries. Results: Among 1 239 474 bicyclist and motorcyclist casualties, the proportion of bicyclists hospitalised for head injuries was higher than that of motorcyclists (10.0% vs 6.5%). However, the multiple logistic regression model shows that, after adjustment of this result for other factors such as helmet use, bicyclists were 18% significantly less likely to be hospitalised for head injuries than motorcyclists (AOR 0.82, 95% CI 0.79 to 0.85). Other important determinants of head injury-related hospitalisation for bicyclists and motorcyclists include female riders, elderly riders, crashes occurring in rural areas, moped riders, riding unhelmeted, intoxicated bicyclists and motorcyclists, unlicensed motorcyclists, dusk and dawn conditions and single-vehicle crashes. Conclusions: Our finding underscores the importance of helmet use in reducing hospitalisation due to head injuries among bicyclists while current helmet use is relatively low.